Increasing young people’s use of sexual and reproductive health services in government health facilities in rural Kenya - Paula Tavrow; Krupa Maria Varghese; Albert Obbuyi; Collins Juma (PLoS ONE, 2026)
Young people in sub-Saharan Africa, especially in rural areas, face numerous daunting geographic and psychosocial barriers to accessing sexual and reproductive health (SRH) services and information. Adolescents worry that providers will be judgmental and not accord them privacy and confidentiality. They are also concerned that community members or extended family may see them waiting for SRH services, which could lead to parental perceptions of promiscuity and punishment. Because they lack comprehensive sexuality education (CSE) in schools, youths often have serious misconceptions about contraceptives. To address these barriers and increase youths’ uptake of SRH services, the After-Hours Adolescent Project (AHAP) was created as a low-cost intervention for rural government health facilities. The main strategies involved extending clinic hours into early evening to be more convenient and confidential for youths, and training newly-graduated nurses to serve as AHAP nurses. AHAP was tested using a randomized cluster design in thirteen government health facilities in Western Kenya. The study examined two intervention types—the full intervention, which included having AHAP nurses conduct CSE classes in nearby schools and community locations; and a partial intervention, which was entirely clinic-based. After one year, AHAP increased young people’s use of SRH services by 87% (full intervention 97%; partial intervention 77%), whereas comparison facilities saw no change. The full intervention facilities also attracted significantly more female and younger SRH clients. Additionally, improved nurse SRH attitudes after AHAP training were sustained. In sum, AHAP was acceptable and effective in rural settings, but requires ongoing budget outlays for nurse salaries.